2016
DOI: 10.3329/agric.v13i1.26560
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Seed Potato (<i>Solanum tuberosum</i> L.) Production and Supply System in Bangladesh - A Review

Abstract: Potato (Solanum tuberosum L.) is an important vegetable that plays a vital role in global food and nutritional security and alleviation of poverty, especially in Bangladesh. Although, the soil and climatic conditions of Bangladesh are favourable for potato cultivation, every year production is hampered due to use of low quality seeds. Seed potato industry is developing in Bangladesh. However, only 5-10% quality seeds are being produced and used by the potato farmers. Quality seeds alone can contribute to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Seed cutting was replaced by planting intact (not cut) tubers in the DSS + treatment as GAP where seeds were cut in the other two treatments (section 2.1.2). The higher price of seeds may indicate that better quality seed was used in DSS + and DSS treatments as seed quality has a profound effect on yields (Shaheb et al 2016). Chemical fertiliser applications in the DSS + and DSS treatments were in accordance with the fertiliser recommendations for soils with a low fertility status and substantially lower in both rates and costs, than the chemical fertilisation applied according to farmers practice (Table 2.4).…”
Section: Other Outcomesmentioning
confidence: 76%
“…Seed cutting was replaced by planting intact (not cut) tubers in the DSS + treatment as GAP where seeds were cut in the other two treatments (section 2.1.2). The higher price of seeds may indicate that better quality seed was used in DSS + and DSS treatments as seed quality has a profound effect on yields (Shaheb et al 2016). Chemical fertiliser applications in the DSS + and DSS treatments were in accordance with the fertiliser recommendations for soils with a low fertility status and substantially lower in both rates and costs, than the chemical fertilisation applied according to farmers practice (Table 2.4).…”
Section: Other Outcomesmentioning
confidence: 76%
“…The use of disease-free seeds can help reduce the transmission of pathogens from propagating materials such as tuber to the field. It has been reported that quality seeds alone can increase yield by 15-20% in Bangladesh [106]. Therefore, micropropagation of potato can help reduce disease transmission through propagating materials; however, little has been achieved on the use of somatic embryos [107], and more researches are required for more remarkable breakthroughs in this regard.…”
Section: Plant Tissue Culture Techniquesmentioning
confidence: 99%
“…It is not only used as a vegetable but also as a cash crop [6], [7]. After rice and wheat, potato is cultivated as the third most important food crop in the world in terms of human consumption [8]- [11]. In the Indian sub-continent, the cultivation of potatoes was probably started during the 17 th century [11]- [13] and in Bangladesh, it was introduced in the late 19 th century [9], [14] - [18].…”
Section: Introductionmentioning
confidence: 99%